A magyarországi szélsőjobboldal és a katolikus egyház viszonya az 1930-as években - Csíky, Balázs (Közép-Európai Közlemények, 2013)
In the 1930s a new extreme right wing tendency appeared in Hungary, the Hungarian National Socialism, which pretended to be Christian in contrast to the German National Socialism. The use of concept of ’Christian’ concealed the differencies and contradictions between the Christianity and the National Socialist ideology which deceived many people. Therefore could be happened that in Hungarian Catholic circles the approach was different to Hungarian National Socialism and to the German version in several cases. Several people did not consider the Hungarian extreme right wing to be dangerous for the Catholic Church but others, among them the apostolic nuncio in Budapest as well, saw the danger of it clearly and noticed the contradiction between the National Socialist ideology and the Catholic teaching. The Hungarian extreme right leaders pretended to be Christian, like Ferenc Szálasi who was leader of the Arrow Cross movement. Szálasi resolved the contradictions between the National Socialist ideology and the Christianity in that way he rejected certain elements of the Christian teaching and formed a special Christianity in himself while he hated the churches and accused those of the falsification of Jesus Christ’s teaching. But seemingly he did not show his mind indeed – probably for tactical reasons – he strove to maintain good relations with the churches. The Catholic bishops called the attention to the danger of extreme ideology but they did not condemn clearly and officially the extreme right organizations. On the other hand the Catholic press wrote clearly that the program of the strongest National Socialist group, the Arrow Cross movement was in contrast to not only the interests but the teaching of the church as well. But the Arrow Cross leaders could maintain the appearance of being Christian. In 1938 several political answers to the strengthening of extreme right were formulated by Catholics. A part of this suggested the compromise with the Arrow Cross movement but others stood by the political reforms on the basis of constitution. As it was drafted by nuncio Rotta as well, it could have been prevented the advance of extreme right ideology with necessary social reforms like agrarian reform. But the reforms were failed until the end of the period.